Remote sensing in support of assessing land-cover changes in Paphos District (Cyprus): a sustainable development project - Hadjimitsis, Diofantos G.; Retalis, Adrianos; Clayton, Chris R I (My University, 2003)
A sustainable development project in which remote sensing is used for assessing landcover changes in Paphos District, Cyprus, was discussed. Landsat-5 TM images acquired in June 1985 and May 2000 were used to derive land cover changes using change detection and classification techniques. The results obtained from this research suggests that the land-cover changes over the 15 years period are apparent and strongly visualized when classification techniques are applied. The comparison between the images acquired on 1985 with the image acquired on 2000, demonstrates the increase of the urbanization especially in the newly established municipalities of Peyia and Polis Chrisochous areas
Keywords: Aerial photography; Sustainable development; Remote sensing